Risk factors and outcomes of IgA nephropathy recurrence after kidney transplantation: a systematic review and meta-analysis - Li, Yue; Tang, Yangming; Lin, Tao; Song, Turun (Frontiers in Immunology, 2023)
Background IgA nephropathy may recur in patients receiving kidney transplantation due to IgA nephropathy induced renal failure. The risk factors for recurrence are still at issue. The aim of this study was to conduct a systematic review and meta-analysis to assess risk factors and outcomes for IgA nephropathy recurrence. Methods We used PubMed, EMBASE, Cochrane Library, Web of Science, Scopus, CNKI, WanFang, VIP and CBM to search for relevant studies published in English and Chinese. Cohort or case-control studies reporting risk factors or outcomes for IgA nephropathy recurrence were included. Results Fifty-eight studies were included. Compare to no recurrence group, those with IgAN recurrence had younger age (mean difference [MD]=-4.27 years; risk ratio [RR]=0.96), younger donor age (MD=-2.19 years), shorter time from IgA nephropathy diagnosis to end stage renal disease (MD=-1.84 years; RR=0.94), shorter time on dialysis (MD=-3.14 months), lower human leukocyte-antigen (HLA) mismatches (MD=-0.11) and HLA-DR mismatches (MD=-0.13). HLA-B46 antigen (RR=0.39), anti-IL-2-R antibodies induction (RR=0.68), mycophenolate mofetil (RR=0.69), and pretransplant tonsillectomy (RR=0.43) were associated with less IgAN recurrence. Of note, male recipient gender (RR=1.17), related donor (RR=1.53), retransplantation (RR=1.43), hemodialysis (RR=1.68), no induction therapy (RR=1.73), mTOR inhibitor (RR=1.51), angiotensin-converting enzyme inhibitors or angiotensin-receptor blockers (RR=1.63) were risk factors for IgAN recurrence. Recurrence increased the risk of graft loss (RR=2.19). Conclusions This study summarized the risk factors for recurrence of IgA nephropathy after kidney transplantation. Well-designed prospective studies are warranted for validation. Systematic Review Registration https://www.crd.york.ac.uk/PROSPERO/display_record.php?RecordID=377480, identifier CRD42022377480.